Eumycetoma Treated With Ketoconazole - Mittal Radha Rani; Gupta Seema (Wolters Kluwer Medknow Publications, 1997)
A 43 year old female had progressive indolent, firm, tender, nodular swellings with multiple sinuses discharging pus containing black granules on left foot and ankle since 3 years. Smear of granule showed dark brown irregular mass with hyphae towards the periphery. Superimposed E. coli infection was treated with cefadroxyl 500 mg B.D Histopathologically marked acanthosis of epidermis , dense collection of mononuclear PMNLâ€s, plasma cells around granules of maduramycosis were seen. X-ray foor showed osteolytic lesions and culture was negative. Satisfactory and progressive improvement occurred after 7 weeks of therapy with ketoconozole 200 mg.